The influence of environmental conditions on the age pattern in breeding performance in a transequatorial migratory seabird - Hernández, Noelia; Genovart, Meritxell; Igual, José Manuel; Oro, Daniel (Frontiers in Ecology and Evolution, 2015)
Several studies of marine top predators, above all of seabirds, have analysed the effects of either individual age or environmental fluctuations on reproduction; nevertheless, little is known about the age patterns in breeding performance in a variable environment. To investigate the simultaneous influence of age and environmental conditions on laying dates and egg volumes, we tested different climate and food availability indices in a transequatorial migratory seabird using female data from a 23-year study. Our results show an initial improvement in breeding parameters with age (i.e. earlier laying dates and greater egg volumes) but no pattern of senescence in older age groups. The best models showed an interaction of time and age in breeding performance, i.e. the age pattern of breeding performance changed each year likely as a result of environmental variability. Nevertheless, climatic indexes used here explained part of that annual variability: NAO and SOI index accounted for 24% and 20% of deviances in laying dates and egg volume respectively. Part of that unexplained variability might be related to other processes such as intermittent breeding and the individual quality of breeders, which were not assessed in our study.